BUDAYA BIROKRASI PEMERINTAH DALAM PELAYANAN PUBLIK - Nurmawan Nurmawan; Dzuldha Yusuf; Ega Ratnasari; Elgan Rachmat Fauzi; Ghina Mardhiyyah N A (Jurnal Inovasi Penelitian, 2021)
This research is motivated by various problems related to the Quality of Administrative Services in the Majalengka Kulon Village Office, Majalengka District, Majalengka Regency. The problem of this research is the limited competence of human resources, which is caused by the culture of the government bureaucracy that has not supported performance so that services are not optimal. The research method used is descriptive qualitative. Data collection techniques used: observation, interviews and literature study. The results showed that the quality of administrative services in Majalengka Kulon Village, Majalengka District, Majalengka Regency was quite good because the results of the study showed that the five aspects had continuously formed a system that complemented each other. So that the service has a good impact in an agency that has superior performance even though there are still obstacles that are less effective.